Twinkle, twinkle, little star - Moroney, Trace (Brimax Publishing Victoria, Australia, 2007)
"Twinkle, Twinkle, Little Star" is a beloved lullaby that marvels at the beauty and mystery of stars in the night sky. It expresses wonder and curiosity about the cosmos, inviting listeners to dream and ponder their place in the universe.